Introduction to linear algebra with applications / Jim DeFranza; Daniel Gagliardi - DeFranza, Jim, 1950-
Offers an introduction to linear algebra. This book features topical coverage and concepts that help provide building blocks and develops sufficient knowledge before moving on. It helps develop abstract thinking. It develops balance between presenting rigor and building intuition. It helps to draw connection between concepts and techniques/facts.